Pengembangan Website Edukasi “WECARE” sebagai Media Pembentukan Karakter Mandiri Siswa Disleksia: Studi Research and Development - Lahizha, Nadia Irsalina; Rahman, Abdul; Dewantara, Brezto Asagi; Rini, Sulistyo (Universitas Muhammadiyah Magelang, 2026)
This study aims to develop the “WECARE” Character Education Website as a digital innovation solution to improve the independent character of dyslexic students based on the characteristics of kinesthetic, visual learning styles, and psychological needs of students. The features are designed to support the formation of independent character according to the reference of student independence. This study uses the Research and Development (R&D) method with the Alessi and Trollip development model consisting of three stages, namely planning, design, and development. The research subjects involved 25 dyslexic children phase D at MTs Al Hamid with consideration of the intensity of digital device use. The development was carried out using Google Sites software as the main cloud-based platform. Data collection was carried out through interviews, observations, and expert validation questionnaires (media, materials, and inclusive education). Feasibility data were analyzed using expert validation. Effectiveness was obtained through the N-Gain score from the comparison of pre-test and post-test scores using 10 statement items. The results showed a feasibility level of 91.6% and an average N-Gain score of 0.706 with a medium to high category.